Eletrophysiological study of the caudal nerve on developing rats - Maia,Juliana Netto (2010)
PURPOSE: To non-invasively study the sensory nerve conduction of the caudal nerve of normal developing rats. METHODS: Twenty normal Wistar male rats served as subjects. Caudal nerve conduction studies were performed at 60 days from birth and weekly at end of six consecutive weeks. The caudal nerve was stimulated distally and nerve potentials were recorded proximally on the animal's tail using common "alligator" clips as surface electrodes. RESULTS: The amplitude and the conduction velocity of the caudal nerve sensory action potential increased linearly from 29±6 µV to 85±13 µV and from 34±3 m/s to 44±4 m/s, respectively, between the 8th and the 15th week of life. The equations of linear regressions were as followed: Amplitude (µV) = 8.1 × weeks - 34 (R² = 0.99) and NCV (m/s) = 1.2 × weeks + 25 (R² = 0.86). CONCLUSIONS: It was possible to study non-invasively the sensitive conduction of the caudal nerve of normal developing rats and describe reference values. The technique and data may be used as animal model in physiological and pathological studies.